2003
DOI: 10.1590/s1516-31802003000300008
|View full text |Cite
|
Sign up to set email alerts
|

Miliary tuberculosis with positive acid-fast bacilli in a pediatric patient

Abstract: Although in some particular cases sputum can be positive for acid-fast bacilli in children, limitations to the sputum test have forced pediatricians to base tuberculosis diagnosis on epidemiological data, clinical findings and radiographic pattern. In this particular case, we hypothesize that the sputum bacillus test was positive because bacilli grew inside residual pneumatoceles that were produced during previous pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[45] A report of miliary tuberculosis after staphylococcal pneumonia was also described in a five-year-old boy whose sputum was found to be positive for AFB. [6]…”
Section: Discussionmentioning
confidence: 99%
“…[45] A report of miliary tuberculosis after staphylococcal pneumonia was also described in a five-year-old boy whose sputum was found to be positive for AFB. [6]…”
Section: Discussionmentioning
confidence: 99%
“…One major pitfall in managing these patients is the misconception that immunisation with BCG can completely eradicate miliary disease and TB meningitis. Miliary TB had been shown to occur in patients with complete immunisation including BCG 24 29. In addition, a meta-analysis reported that the efficacy was only 73% for TB meningitis and 77% for miliary TB 30.…”
Section: Discussionmentioning
confidence: 99%